2019
DOI: 10.18203/2394-6040.ijcmph20190606
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of acute and chronic malnutrition and influence of feeding practices among 6 months to 2 years children in rural field practice area of Kilpauk Medical College, Tamil Nadu

Abstract: Background: In India, 54% of under five children death mainly due to under nutrition. First two years of age is most critical. Nutritional status was assessed by using WHO standard growth chart. Wasting represents acute malnutrition, stunting with chronic, underweight represents both acute and chronic. Based on NFHS-3 data the prevalence of under nutrition rise up to 2 years of age, thereafter more or less stabilizes. Faulty feeding practices plays major role in under nutrition. Hence, this study carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In our study, we found a significant result between pregnancy risk and depression which is supported by the results from the study conducted by Kalra et al 23 About half of the participants had cesarean section pregnancy and majority if the participants were housewives which is similar to the study conducted by Kamali. 24 The prevalence of anxiety in our study is similar to Rezaee and Framarzi. 15 The prevalence of depression in our study was found to be 38.25% which is similar to the study conducted by Lee et al 25 More than one half and more than one-third of the women had antenatal anxiety and depressive symptoms, respectively, in at least one antenatal assessment.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, we found a significant result between pregnancy risk and depression which is supported by the results from the study conducted by Kalra et al 23 About half of the participants had cesarean section pregnancy and majority if the participants were housewives which is similar to the study conducted by Kamali. 24 The prevalence of anxiety in our study is similar to Rezaee and Framarzi. 15 The prevalence of depression in our study was found to be 38.25% which is similar to the study conducted by Lee et al 25 More than one half and more than one-third of the women had antenatal anxiety and depressive symptoms, respectively, in at least one antenatal assessment.…”
Section: Discussionsupporting
confidence: 88%
“…Sailaja et al (2016) [10] found out the prevalence of underweight, stunting, and wasting among infants and young children aged 6 to 24 months to be 44.60, 37.70, and 20.78 per cent respectively. In their study, Dhanalakshmi and Selvaraj (2019) [3] revealed prevalence of underweight, wasting, and stunting was found to be 31.65, 15.00 and 45.60 per cent respectively.…”
Section: Discussionmentioning
confidence: 91%